A randomized controlled study of preoperative oral carbohydrate loading versus fasting in patients undergoing elective craniotomy. Issue 5 (October 2019) - Liu, Bolin; Wang, Yuan; Liu, Shujuan; Zhao, Tianzhi; Zhao, Binfang; Jiang, Xue; Ye, Lin; Zhao, Lanfu; Lv, Wenhai; Zhang, Yufu; Zheng, Tao; Xue, Yafei; et al.
Summary: Object: The aim of this study was to evaluate the effect of preoperative oral carbohydrate loading versus fasting on the outcomes of patients undergoing elective craniotomy. Methods: In a single-center randomized controlled study, 120 neurosurgical patients who were admitted for elective craniotomy were included and randomized into 2 groups: 58 patients received 400 mL of oral carbohydrate loading 2 h before surgery (intervention group), and 62 patients were fasting for 8 h prior to surgery as routine management (control group). The primary end point was glucose homeostasis. Secondary outcomes included handgrip strength, pulmonary function and postoperative complications. Results: Better glucose homeostasis (5.6 ± 1.0 mmol/L vs. 6.3 ± 1.2 mmol/L, P = 0.001) was achieved in patients who received preoperative oral carbohydrate loading compared to fasting. Furthermore, patients in the intervention group had better handgrip strength (25.3 ± 7.1 kg vs. 19.9 ± 7.5 kg, P < 0.0001) and pulmonary function (in terms of peak expiratory flow rate) (315.8 ± 91.5 L/min vs. 270.0 ± 102.7 L/min, P = 0.036) compared to the controls postoperatively. The rates of postoperative surgical and non-surgical complications did not differ between the groups. Both postoperative and total hospital length of stay (LOS) reduced significantly in the intervention group (-3d, P < 0.0001 and P = 0.004). Conclusions: Oral carbohydrate loading given 2 h before surgery in patients undergoing elective craniotomy seems to improve glucose homeostasis, handgrip strength and pulmonary function as well as decrease LOS without increasing the risk of postoperative complications. Routine use of preoperative oral carbohydrate loading could be suggested in clinical settings, though further evaluation of its safety and efficacy is warranted.